2010
DOI: 10.1016/j.nbt.2010.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Mutated genes, pathways and processes in tumours

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution Noncommercial Share Alike 3.0 Unported License, which allows readers to alter, transform, or build upon the article and then distribute the resulting work under the same or similar licence to this one. The work must be attributed back to the original author and commercial use is not permitted without specific permission.Integration of the many available sources of cancer gene information-such as large-scale tumour-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The classical genetic mutations, such as CIN, generally cause alternation of one or more genes, but actual variations involved in cancer are cross-over networks of cell signaling (38). Our discovery confirmed that CIN played myriad roles in tumor initiation and growth orchestrated through the complex regulation of miRNAs on their extensive target genes and the resulting impact on cell signaling.…”
Section: Discussionsupporting
confidence: 65%
“…The classical genetic mutations, such as CIN, generally cause alternation of one or more genes, but actual variations involved in cancer are cross-over networks of cell signaling (38). Our discovery confirmed that CIN played myriad roles in tumor initiation and growth orchestrated through the complex regulation of miRNAs on their extensive target genes and the resulting impact on cell signaling.…”
Section: Discussionsupporting
confidence: 65%
“…Miller dataset) and CGC there is substantial convergence of MutFam driver genes at the level of GO biological processes affected, as also shown in Baudot et al68 . Broadly, MutFams are complementary to Pfam-based methods.…”
supporting
confidence: 71%
“…9,10 Any errors in these processes generating aneuploidy would lead to the miscarriage, age-related infertility, and high incidence of genetic disorders such as Down syndrome in humans. [14][15][16][17] Meiotic cohesin complexes are composed of 4 essential subunits, including a meiosis-specific Smc1 subunit (Smc1b), 2 additional a-kleisins (Rad21L and Rec8) and another stromal antigen protein (Stag3). 18,19 Previous studies have investigated the functions of Smc1b in determining the axis-loop structure of synaptonemal complexes, in providing sister chromatid cohesion in metaphase I and thereafter, in protecting telomere structure, and in synapsis.…”
Section: Discussionmentioning
confidence: 99%